2023
DOI: 10.1038/s12276-023-01023-y
|View full text |Cite
|
Sign up to set email alerts
|

Decorin: a potential therapeutic candidate for ligamentum flavum hypertrophy by antagonizing TGF-β1

Abstract: Ligamentum flavum hypertrophy (LFH) is the main physiological and pathological mechanism of lumbar spinal canal stenosis (LSCS). The specific mechanism for LFH has not been completely clarified. In this study, bioinformatic analysis, human ligamentum flavum (LF) tissues collection and analysis, and in vitro and in vivo experiments were conducted to explore the effect of decorin (DCN) on LFH pathogenesis. Here, we found that TGF-β1, collagen I, collagen III, α-SMA and fibronectin were significantly upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Past studies have demonstrated that collagen I and collagen III are representative fibrotic products [ 25 ]. TGF-β promotes collagen production and induces fibrosis in LF cells [ 26 - 28 ]. These results suggest that PARD3-AS1 may significantly affect the underlying processes and pathophysiology of LFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have demonstrated that collagen I and collagen III are representative fibrotic products [ 25 ]. TGF-β promotes collagen production and induces fibrosis in LF cells [ 26 - 28 ]. These results suggest that PARD3-AS1 may significantly affect the underlying processes and pathophysiology of LFH.…”
Section: Discussionmentioning
confidence: 99%
“…The blots were blocked with 5% skim milk and incubated overnight at 4°C with primary antibodies. These antibodies (Abcam, Cambridge, UK) were prepared in 5% bovine serum albumin as follows: collagen I (1:1,500, ab279711); collagen III (1:1,500, ab6310); transforming growth factor (TGF)-β1 (1:1,500, ab215715), and GAPDH (1:5,000, ab8245) [ 25 - 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…There was no difference between the groups. Several studies ( 27–29 ) have shown that ligamentum flavum hypertrophy is the main causative factor of central spinal stenosis and is involved in long-term chronic compression of the dural sac ( 5 , 30 ). RNRs due to ligamentum flavum hypertrophy-induced spinal stenosis are a chronic process with a high incidence of RNRs.…”
Section: Discussionmentioning
confidence: 99%